"A trade of one's own": The role of social and cultural capital in the success of women in male‐dominated occupations. Issue 2 (5th November 2021) - Bridges, Donna; Bamberry, Larissa; Wulff, Elizabeth; Krivokapic‐Skoko, Branka
Abstract: The skilled trades are highly gender segregated occupations. Unsurprisingly, research about women in this male‐dominated sector focuses on the various barriers to inclusion. In contrast, this article identifies factors that have contributed to women's successes. Drawing on in‐depth interviews with tradeswomen, we found that the success factors for women in the skilled trades were aligned with social and cultural capital. Findings also indicate that women's success is driven by their individual attributes and resources rather than any forms of systematic support. There is limited evidence of a coordinated approach from industry and government to increase gender equity and inclusion. Success for women is, therefore, most likely to be singularly occurring, unpredictable and difficult to replicate. We use a Bourdieusian approach to understand how capital facilitates women's success and how forms of capital can be translated into measurable and repeatable strategies. We argue that capital offers women an opportunity to circumvent traditional resistance to gender inclusion because it provides cultural legitimacy. Replicating social and cultural capital through industry initiatives that are measurable and repeatable are likely to be the most constructive ways forward. We recommend a coordinated industry approach to improve diversity and inclusion in the sector.